Bi-NiO@Bi2MoO6 photocatalyst with dual active sites and its applications

CN122937819APending Publication Date: 2026-10-20CHONGQING NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611085706.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0007]针对现有Bi2MoO6光催化剂载流子分离效率差、活性氧物种不可控、NO2副产物累积严重、硝酸盐选择性低、O2活化受自旋禁阻限制、贵金属改性成本高、单活性位点性能瓶颈突出以及粉体难以工程应用等技术问题,本发明提供一种局域等离子体与自旋极化协同的双活性位点Bi-NiO@ Bi2MoO6光催化剂及其制备方法

Benefits of technology

(1)本发明首次通过原位还原策略在层状Bi2MoO6上同步构筑金属Bi纳米颗粒与NiO颗粒双活性位点,实现了等离子体光增强效应与自旋极化电子调控效应的融合,设计思路新颖,突破了传统单活性位点改性的性能瓶颈。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1784624625457-000001
    Figure REF-OBJ-1784624625457-000001
  • Figure REF-OBJ-1784624625457-000002
    Figure REF-OBJ-1784624625457-000002
  • Figure REF-OBJ-1784624625457-000003
    Figure REF-OBJ-1784624625457-000003
Patent Text Reader

Abstract

This invention discloses a dual-active-site Bi-NiO@Bi2MoO6 photocatalyst and its applications. The Bi-NiO@Bi2MoO6 photocatalyst comprises a layered Bi2MoO6 substrate, metallic Bi nanoparticles, and NiO particles. The metallic Bi nanoparticles and NiO particles are in situ distributed on the surface and / or inside the layered Bi2MoO6 substrate. This invention utilizes the localized surface plasmon resonance effect of metallic Bi to enhance visible light absorption and hot electron generation, and utilizes the spin polarization characteristics of NiO to construct a spin-selective electron transfer channel. Through the synergistic effect of plasmon resonance and spin polarization, efficient separation of photogenerated carriers is achieved, breaking the spin-forbidden restriction of O2 activation and directionally constructing ·O2. ‑ The dominant oxidation pathway.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of environmental functional photocatalytic materials technology and air pollution control technology, specifically relating to a Bi-NiO@Bi2MoO6 photocatalyst with localized plasma and spin polarization synergy and its preparation method, a supported monolithic photocatalytic material and its application in nitrogen oxide purification. Background Technology

[0002] Nitrogen oxides (NOx) are among the major air pollutants and important precursors to photochemical smog, acid rain, and fine particulate matter (PM2.5), posing a serious threat to the atmospheric environment and human health. Semiconductor photocatalysis technology has attracted widespread attention due to its ability to utilize renewable and clean solar energy to achieve deep mineralization of pollutants under mild conditions. Among numerous photocatalytic materials, bismuth molybdate (Bi2MoO6), a typical Aurivillius-type layered oxide semiconductor, possesses a unique layered crystal structure, a suitable bandgap width (approximately 2.7 eV), and good visible light response, demonstrating its application potential in the photocatalytic removal of NOx.

[0003] However, pure-phase Bi₂MoO₆ photocatalysts still have the following prominent problems: First, the high recombination rate of photogenerated electron-hole pairs and low quantum efficiency result in extremely low NO photocatalytic removal activity; second, limited light absorption capacity leads to insufficient visible light utilization efficiency; third, conventional photocatalytic systems struggle to directionally generate superoxide radicals (·O₂). - This leads to an uncontrollable NO oxidation pathway, easily generating toxic NO2 byproducts, and low nitrate selectivity.

[0004] To overcome these shortcomings, researchers have attempted to modify Bi₂MoO₆ using strategies such as heterostructure construction, elemental doping, defect engineering, and noble metal deposition. For example, one study modified Bi₂MoO₆ through the synergistic effect of N ions, Bi, and oxygen vacancies, increasing its NO purification activity to 8.9 times that of pure Bi₂MoO₆. However, these modification strategies still have limitations: on the one hand, while noble metal (such as Au, Ag, and Pt) plasma modification can enhance light absorption, it is costly and economically unfeasible; on the other hand, non-noble metal unit-point modification cannot simultaneously achieve effective control of broadband visible light capture and electron transfer processes.

[0005] More importantly, in the photocatalytic oxidation of NO, ·O2 - The generation efficiency directly determines the NO removal efficiency and product selectivity. However, the ground-state oxygen molecule (O2) has a triplet electronic configuration, while the electrons generated by photocatalyst excitation are singlet. This spin mismatch leads to the activation of O2 to generate ·O2. -The process is severely constrained by the spin-forbidden effect. Conventional photocatalytic systems cannot effectively overcome this spin-forbidden restriction, leading to the limitations of O2. - The hindered generation kinetics limit the deep oxidation of NO. Although a single metallic Bi plasma site can enhance light absorption and hot electron generation, it cannot modulate the spin electron channel, making it difficult to overcome the challenges in NO oxidation kinetics.

[0006] To address the shortcomings of the existing technologies, there is an urgent need to develop a novel photocatalyst and an engineerable preparation method that can simultaneously achieve broad-spectrum light absorption enhancement, efficient carrier separation, spin-forbidden effect elimination, and highly selective deep oxidation of NO. Summary of the Invention

[0007] To address the technical problems of existing Bi2MoO6 photocatalysts, such as poor carrier separation efficiency, uncontrollable reactive oxygen species, severe accumulation of NO2 byproducts, low nitrate selectivity, spin-forbidden limitation of O2 activation, high cost of noble metal modification, prominent performance bottleneck of single active sites, and difficulty in engineering applications of powder, this invention provides a dual-active-site Bi-NiO@Bi2MoO6 photocatalyst with localized plasma and spin polarization synergy and its preparation method.

[0008] This invention employs an in-situ reduction strategy to simultaneously construct dual active sites for metallic Bi nanoparticles and NiO particles on a layered Bi₂MoO₆ substrate. It leverages the localized surface plasmon resonance effect of metallic Bi to enhance visible light absorption and hot electron generation, while utilizing the spin polarization properties of NiO to construct a spin-selective electron transfer channel. Through the synergistic effect of plasmon resonance and spin polarization, it achieves efficient separation of photogenerated carriers, overcomes the spin-forbidden restriction of O₂ activation, and directionally constructs O₂. - The dominant oxidation pathway. Simultaneously, this invention provides a PTFE-assisted ceramic foam supported molding process to fabricate powder catalysts into monolithic catalytic modules, offering a scalable and engineerable photocatalytic technology solution for the efficient and selective treatment of low-concentration NOx at room temperature.

[0009] To achieve the above objectives, the present invention adopts the following technical solution: This invention discloses a dual-active-site Bi-NiO@Bi2MoO6 photocatalyst, wherein the Bi-NiO@Bi2MoO6 photocatalyst comprises a layered Bi2MoO6 substrate, metallic Bi nanoparticles and NiO particles, wherein the metallic Bi nanoparticles and NiO particles are in situ distributed on the surface and / or inside the layered Bi2MoO6 substrate.

[0010] This invention discloses a method for preparing the above-mentioned dual-active-site Bi-NiO@Bi2MoO6 photocatalyst, comprising the following steps: (1) Preparation of layered Bi2MoO6 substrate; (2) Disperse the Bi2MoO6 obtained in step (1) with the nickel salt in a solvent; (3) Add a reducing agent to the system obtained in step (2) to carry out a reduction reaction; (4) After the reaction is completed, the Bi-NiO@Bi2MoO6 photocatalyst is obtained by separation, washing and drying.

[0011] As a preferred technical solution, the preparation method of layered Bi2MoO6 in step (1) is a hydrothermal method, which specifically includes: dissolving bismuth salt and molybdate in water and carrying out a hydrothermal reaction at a temperature of 160-200°C for 12-20 hours.

[0012] As a preferred technical solution, the bismuth salt is bismuth nitrate pentahydrate, and the molybdate is sodium molybdate dihydrate; the molar ratio of the bismuth salt to the molybdate is 2:1.

[0013] As a preferred technical solution, the nickel salt in step (2) is nickel chloride hexahydrate; the solvent in step (2) is water; and the reducing agent in step (3) is sodium borohydride solution.

[0014] As a preferred technical solution, the ratio of nickel salt to Bi2MoO6 in step (2) is (0.05~0.25)g : 0.5g.

[0015] As a preferred technical solution, the ratio of nickel salt to Bi2MoO6 in step (2) is (0.1~0.2)g : 0.5g.

[0016] The present invention also discloses a supported monolithic photocatalytic material comprising the aforementioned Bi-NiO@Bi2MoO6 photocatalyst and a porous support, wherein the Bi-NiO@Bi2MoO6 photocatalyst is supported on the surface of the porous support.

[0017] As a preferred technical solution, the porous carrier is alumina foam ceramic, glass fiber mesh, activated carbon, or honeycomb ceramic.

[0018] The present invention also discloses the application of the Bi-NiO@Bi2MoO6 photocatalyst or the supported monolithic photocatalytic material in the photocatalytic degradation of nitrogen oxides.

[0019] The beneficial effects of this invention are as follows: (1) This invention is the first to construct dual active sites of metal Bi nanoparticles and NiO particles on layered Bi2MoO6 by means of in-situ reduction strategy, realizing the fusion of plasma light enhancement effect and spin polarization electronic regulation effect. The design idea is novel and breaks through the performance bottleneck of traditional single active site modification.

[0020] (2) This invention utilizes the spin polarization properties of NiO to break the spin-forbidden restriction of O2 molecules, thus solving the problem of traditional materials O2 from the electronic spin level. - The core challenge of low generation efficiency provides a new technological path for the targeted generation of highly efficient reactive oxygen species.

[0021] (3) This invention broadens the visible light response range and enhances the light-harvesting ability through the local surface plasmon resonance effect of metallic Bi. At the same time, it suppresses the recombination of photogenerated excitons and charge carriers through the synergistic effect of dual active sites, thus significantly improving the photocatalytic quantum efficiency.

[0022] (4) The optimized Bi-NiO@Bi2MoO6 photocatalyst of the present invention achieves excellent performance with NO removal rate of 77.0%, nitrate selectivity of 76.7%, and NO2 by-product concentration of less than 11 ppb. Its catalytic activity is 9.7 times that of pure Bi2MoO6, and the performance improvement is significant.

[0023] (5) The present invention uses non-precious metal modification (Bi and Ni are both inexpensive metals) throughout the process, replacing expensive metals such as Au, Ag, and Pt. The raw materials are inexpensive and readily available, the preparation process is simple and mild, there are no toxic by-product emissions, it is green and environmentally friendly, and it is suitable for industrial mass production.

[0024] (6) By adjusting the amount of nickel chloride hexahydrate (0.05-0.25 g / 0.5 g Bi2MoO6), the loading of NiO (5%-25%) can be gradient controlled, thereby achieving continuous adjustment and directional optimization of catalytic performance.

[0025] (7) The present invention is equipped with PTFE-assisted ceramic foam loading molding technology to make the powder catalyst into an integral catalytic module. After loading, the NO removal efficiency can reach 84%, which effectively solves the problems of easy dispersion, loss and agglomeration of powder catalyst. The material has strong stability and has practical engineering application value.

[0026] (8) This invention clarifies the regulatory role of plasma-spin synergy in the generation and charge transfer of reactive oxygen species, providing a general strategy that can be referenced for the rational design of highly selective denitrification photocatalysts. Attached Figure Description

[0027] To make the objectives, technical solutions, and beneficial effects of this invention clearer, the following figures are provided for illustration: Figure 1 SEM images of BMO, Bi@BMO, and Bi-NiO@BMO.

[0028] Figure 2 TEM images of BMO, Bi@BMO, and Bi-NiO@BMO.

[0029] Figure 3 This is a spherical aberration electron microscopy image of Bi-NiO@BMO.

[0030] Figure 4 XPS Ni 2p spectrum of Bi-NiO@BMO.

[0031] Figure 5 This is a comparison of the photocurrent and UV-Vis absorption properties of the samples.

[0032] Figure 6 The image shows the XRD pattern of the catalyst.

[0033] Figure 7 This is a graph from a free radical scavenger test.

[0034] Figure 8 This is a graph showing the NO removal efficiency of the catalyst.

[0035] Figure 9 This is a comparison chart of NO2 byproduct concentrations.

[0036] Figure 10 This is a long-term reaction activity diagram of photocatalytic degradation of NO supported on foam ceramics. Detailed Implementation

[0037] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.

[0038] Example 1: Preparation of layered Bi2MoO6 substrate 1 mmol sodium molybdate dihydrate and 2 mmol bismuth nitrate pentahydrate were dissolved in 60 mL distilled water and magnetically stirred for 30 min to ensure complete dissolution. The mixture was then transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor and placed in an oven at 180 ℃ for hydrothermal incubation for 16 h. After natural cooling to room temperature, the precipitate was separated by centrifugation and washed repeatedly with deionized water and anhydrous ethanol. The washed precipitate was then dried in an oven at 60 ℃ for 12 h to obtain a pure phase layered Bi2MoO6 sample.

[0039] Example 2: Preparation of Bi-NiO@BMO with dual active sites Take 0.5 g of Bi2MoO6 sample prepared in Example 1, add different masses of nickel chloride hexahydrate (0.05 g, 0.1 g, 0.15 g, 0.2 g, 0.25 g), disperse in 30 mL of distilled water, and stir magnetically until uniformly dispersed; add 20 mL of 70 mmol / L sodium borohydride solution, and stir magnetically for 1 h to reduce the reaction; after the reaction is complete, centrifuge and filter to collect the precipitate, wash with deionized water and anhydrous ethanol 2-3 times each, and dry at 60 ℃ for 12 h to obtain Bi-NiO@Bi2MoO6 photocatalysts with different NiO loadings (denoted as Bi-NiO@BMO-5%, Bi-NiO@BMO-10%, Bi-NiO@BMO-15%, Bi-NiO@BMO-20%, Bi-NiO@BMO-25%).

[0040] Example 3: Preparation of Supported Monolithic Photocatalytic Materials The Bi-NiO@BMO photocatalyst (Bi-NiO@BMO-15%) prepared in Example 2 was mixed with an appropriate amount of anhydrous ethanol, and an appropriate amount of PTFE emulsion was added. The mixture was ultrasonically dispersed to form a stable suspension. The suspension was slowly dripped onto the surface of an alumina foam ceramic substrate to ensure that the suspension uniformly covered the substrate surface. The loaded foam ceramic was dried in a 60 °C oven to obtain a supported monolithic photocatalytic material.

[0041] Comparative Example 1: Preparation of pure-phase BMO Layered Bi2MoO6 samples (BMO) were prepared according to the method in Example 1 without subsequent reduction modification and used as control samples.

[0042] Comparative Example 2: Preparation of Bi@BMO modified with single metal Bi Take 0.5 g of the Bi2MoO6 sample prepared in Example 1 and disperse it in 30 mL of distilled water; add 20 mL of 70 mmol / L sodium borohydride solution and magnetically stir the reduction reaction for 1 h; centrifuge and filter, wash twice with deionized water and anhydrous ethanol, and dry at 60 °C for 12 h to obtain the Bi2MoO6 photocatalyst modified with single metal Bi (Bi@BMO).

[0043] Performance Tests and Results (1) Microscopic morphological characterization The BMO prepared in Comparative Example 1, the Bi@BMO prepared in Comparative Example 2, and the Bi-NiO@BMO (Bi-NiO@BMO-15%) prepared in Example 2 were characterized by SEM and TEM. The results are as follows: Figure 1 and Figure 2As shown: pure Bi2MoO6 exhibits a typical layered structure; in the Bi@BMO sample, metallic Bi nanoparticles are uniformly distributed on the surface of Bi2MoO6; in the Bi-NiO@BMO sample, metallic Bi nanoparticles and ultra-small NiO particles are both distributed in situ on the surface and / or inside of Bi2MoO6, forming a dual-active-site co-modification structure.

[0044] The Bi-NiO@BMO (Bi-NiO@BMO-15%) prepared in Example 2 was characterized by spherical aberration electron microscopy, and the results are as follows: Figure 3 As shown, the high-resolution images clearly display the lattice fringes of Bi2MoO6, the lattice fringes of metallic Bi nanoparticles, and the lattice fringes of ultrasmall NiO particles, further confirming the successful construction of dual active sites.

[0045] (2) Characterization of surface chemical state The Bi-NiO@BMO (Bi-NiO@BMO-15%) prepared in Example 2 was characterized by XPS Ni 2p, and the results are as follows: Figure 4 As shown, Ni appears in the Ni 2p spectrum. 2+ The characteristic peaks indicate that nickel exists in the form of NiO, and that there is an interfacial electronic interaction between NiO and Bi2MoO6.

[0046] (3) Crystal structure characterization The BMO prepared in Comparative Example 1, the Bi@BMO prepared in Comparative Example 2, and the Bi-NiO@BMO prepared in Example 2 were characterized by XRD, and the results are as follows: Figure 6 As shown, the XRD pattern of Bi-NiO@BMO simultaneously exhibits characteristic diffraction peaks of Bi2MoO6, metallic Bi, and NiO, and no other impurity phases were detected, indicating that the Bi-NiO@BMO composite material was successfully prepared.

[0047] (4) Photoelectric performance characterization The photocurrent response and UV-Vis absorption spectra of BMO prepared in Comparative Example 1, Bi@BMO prepared in Comparative Example 2, and Bi-NiO@BMO (Bi-NiO@BMO-15%) prepared in Example 2 were measured, and the results are as follows. Figure 5 As shown, the photocurrent density of Bi-NiO@BMO is significantly higher than that of pure Bi2MoO6 and Bi@BMO, indicating that the synergistic effect of the dual active sites effectively promotes the separation and transport of photogenerated charges. Meanwhile, the absorption intensity of Bi-NiO@BMO in the visible light region is significantly enhanced, which is attributed to the localized surface plasmon resonance effect of metallic Bi.

[0048] (5) Analysis of reactive oxygen species The Bi-NiO@BMO (Bi-NiO@BMO-15%) prepared in Example 2 was subjected to free radical scavenging agent testing and electron spin resonance (ESR) testing. The results are as follows: Figure 7 As shown, both the quenching experiment and ESR results confirm that the ·O2 content in the Bi-NiO@BMO photocatalytic system is optimal. - As the absolutely dominant reactive oxygen species, ·O2 - It is the core active species driving the deep oxidation of NO, which is attributed to the effective breaking of the spin-forbidden effect of O2 activation by the spin polarization characteristics of NiO.

[0049] (6) Photocatalytic NO removal performance test Under visible light irradiation, the NO photocatalytic removal efficiency of BMO prepared in Comparative Example 1, Bi@BMO prepared in Comparative Example 2, and Bi-NiO@BMO prepared in Example 2 were tested respectively. The results are as follows: Figure 8 As shown, the NO removal efficiency of pure Bi₂MoO₆ is extremely low (approximately 7.9%). The NO removal efficiency of Bi@BMO is improved somewhat, but still limited. The NO removal efficiency of Bi-NiO@BMO prepared in Example 2 is significantly higher than that of pure Bi₂MoO₆ and Bi@BMO. Among them, Bi-NiO@BMO-10%, Bi-NiO@BMO-15%, and Bi-NiO@BMO-20% have relatively high NO removal efficiencies, especially Bi-NiO@BMO-15%, which has the highest NO removal efficiency at 77.0%, 9.7 times that of pure Bi₂MoO₆.

[0050] (7) Selectivity analysis of NO2 byproducts and nitrates The concentration of NO2 byproducts during the photocatalytic NO oxidation process of each sample was detected, and the results are as follows: Figure 9 As shown, pure Bi₂MoO₆ has a high cumulative concentration of NO₂ byproducts, while the Bi-NiO@BMO prepared in Example 2 has a NO₂ byproduct concentration of less than 11 ppb, with a nitrate selectivity of 76.7%. This indicates that the Bi-NiO@BMO dual-active-site system effectively inhibits the formation of toxic NO₂ byproducts and achieves highly selective conversion of NO to nitrates.

[0051] (8) Stability test of load-bearing monolithic materials The supported monolithic photocatalytic material prepared in Example 3 was subjected to a long-term photocatalytic degradation experiment of NO, and the results are as follows: Figure 10 As shown, during continuous long-term reactions, the supported monolithic material maintained a stable NO removal efficiency (up to 84%), and the catalyst did not experience significant detachment. This result fully demonstrates that the PTFE-assisted ceramic foam loading process can effectively fix the catalyst powder, meeting the requirements of material stability and durability for engineering applications.

[0052] Characterization methods including XRD, SEM, TEM, XPS, and photocurrent response confirmed that metallic Bi nanoparticles and NiO particles were successfully co-modified in situ on the surface of layered Bi₂MoO₆ (see above). Figures 1 to 6 Photocatalytic NO removal performance tests showed that the Bi-NiO@BMO photocatalyst achieved a maximum NO removal rate of 77.0%, with catalytic activity 9.7 times that of pure Bi₂MoO₆ (see [reference]). Figure 8 ).

[0053] The above-described embodiments are merely preferred embodiments provided to fully illustrate the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are all within the scope of protection of the present invention. The scope of protection of the present invention is defined by the claims.

Claims

1. A dual-active-site Bi-NiO@Bi2MoO6 photocatalyst, characterized in that: The Bi-NiO@Bi2MoO6 photocatalyst comprises a layered Bi2MoO6 substrate, metallic Bi nanoparticles, and NiO particles, wherein the metallic Bi nanoparticles and NiO particles are in situ distributed on the surface and / or inside the layered Bi2MoO6 substrate.

2. The preparation method of the dual-active-site Bi-NiO@Bi2MoO6 photocatalyst according to claim 1, characterized in that: Includes the following steps: (1) Preparation of layered Bi2MoO6 substrate; (2) Disperse the Bi2MoO6 obtained in step (1) with the nickel salt in a solvent; (3) Add a reducing agent to the system obtained in step (2) to carry out a reduction reaction; (4) After the reaction is completed, the Bi-NiO@Bi2MoO6 photocatalyst is obtained by separation, washing and drying.

3. The preparation method of the dual-active-site Bi-NiO@Bi2MoO6 photocatalyst according to claim 2, characterized in that: The preparation method of layered Bi2MoO6 in step (1) is a hydrothermal method, which specifically includes: dissolving bismuth salt and molybdate in water and carrying out a hydrothermal reaction at a temperature of 160-200℃ for 12-20h.

4. The preparation method of the dual-active-site Bi-NiO@Bi2MoO6 photocatalyst according to claim 3, characterized in that: The bismuth salt is bismuth nitrate pentahydrate, and the molybdate is sodium molybdate dihydrate; the molar ratio of the bismuth salt to the molybdate is 2:

1.

5. The preparation method of the dual-active-site Bi-NiO@Bi2MoO6 photocatalyst according to claim 2, characterized in that: In step (2), the nickel salt is nickel chloride hexahydrate; in step (2), the solvent is water; and in step (3), the reducing agent is sodium borohydride solution.

6. The preparation method of the dual-active-site Bi-NiO@Bi2MoO6 photocatalyst according to claim 2, characterized in that: In step (2), the ratio of nickel salt to Bi2MoO6 is (0.05~0.25)g : 0.5g.

7. The preparation method of the dual-active-site Bi-NiO@Bi2MoO6 photocatalyst according to claim 6, characterized in that: In step (2), the ratio of nickel salt to Bi2MoO6 is (0.1-0.2)g : 0.5g.

8. A supported monolithic photocatalytic material, characterized in that: The invention comprises the Bi-NiO@Bi2MoO6 photocatalyst as described in claim 1, and a porous support, wherein the Bi-NiO@Bi2MoO6 photocatalyst is supported on the surface of the porous support.

9. The supported monolithic photocatalytic material according to claim 8, characterized in that: The porous carrier is alumina foam ceramic, glass fiber mesh, activated carbon, or honeycomb ceramic.

10. The application of the Bi-NiO@Bi2MoO6 photocatalyst of claim 1, or the supported monolithic photocatalytic material of claim 8 or 9, in the photocatalytic degradation of nitrogen oxides.